The Growth and Flowering of Potted Chrysanthemum (Chrysanthemum morifolium Ramat) on Types of Organic Media and Watering Frequent - Ika Rahmawati; Endang Sulistyaningsih (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2019)
The soils in Samigaluh are mostly dominated by clay and used by farmer for crops production. The growing media for potted chrysanthemum requires additional organic media that could be mixed with the organic material to improve chemical and physical soil properties. Furthermore, the research location is a region with little water in dry season. The research aimed to determine the growth and flower yield response of Avanthe agrihorti to the different organic material mixed with clay and watering frequency. The research was arranged in a split plot design with 3 replications, conducted at an altitude of 462 m above sea level in the village of Gerbosari, Samigaluh, from March to June 2018. The main plot was watering frequency, i.e. every day, every three days and every five days. The subplot was types of media, i.e. clay + manure, clay + manure + cocopeat, clay + manure +rice husk, and clay + manure + rice husk charcoal. Data on the growth and yield of chrysanthemum plants were observed and statistically analyzed with ANOVA and continued with DMRT test at 5%. The results showed that the types of media and watering frequency did not significantly give different effect on most of the observed variables. However, Avanthe Agrihorti planted on clay + manure + cocopeat at all watering frequencies showed better growth and yield of flowers than those planted on other media. The efficient watering frequency for Avanthe Agrihorti was every three days. This study provides information for farmers on an alternative method to prepare the best media for the cultivation of potted chrysanthemum on the soil clay.